A Literature Review on Curriculum Progress at Yamama Junior High School: A National Education Perspective - Sandi, Galuh; Muhammad, Ulul Azmi; Yudisthira, Ardhi; Amala, Istiqomah Ahsanu (Medan Resource Center, 2024)
The curriculum is an essential component of the education system, aiming to achieve national education goals. This article discusses the progress of the curriculum at Yamama Junior High School in relation to national education policies, which continue to evolve. The curriculum has adapted from the Education Unit Level Curriculum (KTSP) to the 2013 Curriculum (K-13), and then to the Independent Curriculum. These adaptations help improve the quality of education and align learning with student needs and national education goals. The method used in this study is a literature review to analyze the implementation of the existing curriculum at Yamama Junior High School, as well as the challenges and opportunities within the Indonesian educational context. Yamama Junior High School has successfully adapted to changes in the national curriculum, including the Independent Curriculum, which aims to enhance the quality of education and the relevance of learning.